Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1055/s-0042-107472
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Antioxidant Potential of the Phytonutrient-Rich Decoction of Cichorium spinosum and C. intybus

Abstract: The Cretan diet, as the basis of the Mediterranean diet, has provided traditional remedies for the general well being of people through the long-established consumption of cooked wild greens and vegetables. The intake of the water decoctions of Cichorium spinosum and Cichorium intybus in the context of the daily dietary regime in Greece has been long associated with "liver detoxifying" properties. In the current study, we performed an in-depth investigation of the water decoctions traditionally prepared from C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 45 publications
3
30
0
1
Order By: Relevance
“…The increase in antioxidant activity at the 3rd growth stage is highly associated with the increased content of bioactive compounds, such as ascorbic acid, phenolic acids and total phenolic compounds (Tables 2 and 5), whereas tocopherols content seems that is not significantly correlated with the antioxidant properties of C. spinosum leaves (Table 3). Similar results have been reported by Brieudes et al (2016), who evaluated the antioxidant properties of water decoctions of C. spinosum leaves and suggested a significant correlation of antioxidant potency with phenolic compounds. Pereira, Barros, Carvalho, and Ferreira (2011) have also suggested phenolic compounds content to be linearly correlated with antioxidant activity of various wild edible greens, with different correlations between the various classes of phenolic compounds and the tested assays.…”
Section: Tablesupporting
confidence: 89%
See 2 more Smart Citations
“…The increase in antioxidant activity at the 3rd growth stage is highly associated with the increased content of bioactive compounds, such as ascorbic acid, phenolic acids and total phenolic compounds (Tables 2 and 5), whereas tocopherols content seems that is not significantly correlated with the antioxidant properties of C. spinosum leaves (Table 3). Similar results have been reported by Brieudes et al (2016), who evaluated the antioxidant properties of water decoctions of C. spinosum leaves and suggested a significant correlation of antioxidant potency with phenolic compounds. Pereira, Barros, Carvalho, and Ferreira (2011) have also suggested phenolic compounds content to be linearly correlated with antioxidant activity of various wild edible greens, with different correlations between the various classes of phenolic compounds and the tested assays.…”
Section: Tablesupporting
confidence: 89%
“…Moreover, total phenolic compounds consisted mostly of phenolic acids, especially in the 3rd growth stage where 80% of total phenolic compounds were phenolic acids. Both compounds have been associated with various bioactive effects such as antiinflammatory, antioxidant and anti-obesity properties, while in vitro studies have confirmed their antidiabetic effects (Brieudes et al, 2016;Zhu, Wang, Du, Liu, & Liu, 2015). Therefore, considering the high content of leaves in these compounds at late developmental stages (3rd stage), alternative uses for pharmaceutical purposes can be proposed.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Other important compounds with bioactive properties are tocopherols, which are present in plant tissues in various isoforms, and their content may be also regulated through the nutrient solution composition . However, despite the beneficial effects of the various bioactive compounds detected in wild edible plants, several toxicity symptoms have been reported; therefore, cytotoxicity studies against normal and cancer cells have to be carried out prior to suggesting the consumption of such species …”
Section: Introductionmentioning
confidence: 99%
“…The presence of CQAs under mono and di-caffeoylquinic acids forms has been previously described by Milala et al (2009). The high content of chicoric acid rather described in lower quantity in roots than in the aerial parts of chicory (Al-Snafi et al, 2016;Brieudes et al, 2016) shows that the chromatography procedure we used allows to concentrate the caffeoyl derivatives. The presence of quercetin-3-O-glucuronide in NCRAE was described in the roots of chicory (Schultz et al, 2005).…”
Section: Discussionmentioning
confidence: 99%